EpCAM(high) and EpCAM(low) circulating tumor cells in metastatic prostate and breast cancer patients - de Wit, Sanne (Oncotarget, 2018)
The presence of high expressing epithelial cell adhesion molecule (EpCAM(high)) circulating tumor cells (CTC) enumerated by CellSearch(®) in blood of cancer patients is strongly associated with poor prognosis. This raises the question about the presence and relation with clinical outcome of low EpCAM expressing CTC (EpCAM(low) CTC). In the EU-FP7 CTC-Trap program, we investigated the presence of EpCAM(high) and EpCAM(low) CTC using CellSearch, followed by microfiltration of the EpCAM(high) CTC depleted blood. Blood samples of 108 castration-resistant prostate cancer patients and 22 metastatic breast cancer patients were processed at six participating sites, using protocols and tools developed in the CTC-Trap program. Of the prostate cancer patients, 53% had ≥5 EpCAM(high) CTC and 28% had ≥5 EpCAM(low) CTC. For breast cancer patients, 32% had ≥5 EpCAM(high) CTC and 36% had ≥5 EpCAM(low) CTC. 70% of prostate cancer patients and 64% of breast cancer patients had in total ≥5 EpCAM(high) and/or EpCAM(low) CTC, increasing the number of patients in whom CTC are detected. Castration-resistant prostate cancer patients with ≥5 EpCAM(high) CTC had shorter overall survival versus those with <5 EpCAM(high) CTC (p = 0.000). However, presence of EpCAM(low) CTC had no relation with overall survival. This emphasizes the importance to demonstrate the relation with clinical outcome when presence of CTC identified with different technologies are reported, as different CTC subpopulations can have different relations with clinical outcome.